100k views
20 votes
Which expression is equivalent to 2(x -1)+x

A. 3x-1


B. 3x-2


C. 2x


D. 2x-1

Solve ASAP point theif = BAN!

User Jasiu
by
4.6k points

2 Answers

10 votes

Answer:

  • Option B

Explanation:

First, let's simplify the given expression.

  • => 2(x - 1) + x
  • => 2x - 2 + x
  • => (2x + x) - 2
  • => 3x - 2

Looking at all the options, we can say that Option B is correct.

User Mel Green
by
4.5k points
5 votes


\huge\text{Hey there!}


\huge\textbf{Question reads....}


\large\text{Which expression is equivalent to 2(x - 1) + x?}


\huge\textbf{Step by step to find your result}


\large\textbf{First you have to DISTRIBUTE 2 WITHIN the}\\\large\textbf{PARENTHESES}


\large\text{2(x - 1) + x}\\\rightarrow\large\text{2(x) + 2(-1) + x}\\\rightarrow\large\text{2x - 2 + x}\\\rightarrow\large\text{2x - 2 + 1x}\\\rightarrow\large\textbf{COMBINE the LIKE TERMS}\leftarrow\\\rightarrow\large\text{(2x + 1x) - (2)}\\\rightarrow\large\text{3x - 2}


\huge\textbf{FINALLY WE HAVE YOUR RESULT}


\huge\boxed{\textsf{Therefore, your answer is: }}}\\\huge\boxed{\mathsf{Option\ B. \ 3x - 2}}\huge\checkmark


\huge\text{Good luck on your assignment \& enjoy }\\\huge\text{your day!}

~
\frak{Amphitrite1040:)}

User Predator
by
4.9k points